Best Answer

x + 8y = 3 therefore 2x + 16y = 6 (a)

2x + 3y = -7 (b)

Subtract (b) from (a): 13y = 13 so y = 1 and x = -5

Q: How can you solve this elimination x plus 8y equals 3 2x plus 3y equals -7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

y=16 x= -4

(2,-2)

Yes and it works out that x = 3 and y = 4

2x+a=p 2x=p-a x=.5p-.5a

2x + 2y = 44x + y = 1There are many methods you can use to solve this system of equations (graphing, elimination, substitution, matrices)...but no matter what method you use, you should get x = -1/3 and y = 7/3.

Related questions

y=16 x= -4

(2,-2)

Yes and it works out that x = 3 and y = 4

2x+a=p 2x=p-a x=.5p-.5a

y= -2x

2x + 2y = 44x + y = 1There are many methods you can use to solve this system of equations (graphing, elimination, substitution, matrices)...but no matter what method you use, you should get x = -1/3 and y = 7/3.

3

Usually elimination is used on two equations and is called linear combination. You could solve for "y." That is customary. 2x+3y=1 3y=-2y+1 y=(-2/3)x+1/3

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

8

many solutions

(3,3)